2012
DOI: 10.1111/nin.12007
|View full text |Cite
|
Sign up to set email alerts
|

Client–provider relationships in a community health clinic for people who are experiencing homelessness

Abstract: Recognizing the importance of health-promoting relationships in engaging people who are experiencing homelessness in care, most research on health clinics for homeless persons has involved some recognition of client-provider relationships. However, what has been lacking is the inclusion of a critical analysis of the policy context in which relationships are enacted. In this paper, we question how client-provider relationships are enacted within the culture of community care with people who are experiencing hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Previous studies have identified a similar sense of conditionality to care (e.g. Oudshoorn et al, 2013), whilst Thompson et al, (2004) framed this differently, as the necessity for 'willingness' from service users. This would support a view that the required compliance, proposed by those in the current study, could also be viewed by services as a need for 'engagement', locating the problem within the service user.…”
Section: Conditions Of Helpmentioning
confidence: 99%
“…Previous studies have identified a similar sense of conditionality to care (e.g. Oudshoorn et al, 2013), whilst Thompson et al, (2004) framed this differently, as the necessity for 'willingness' from service users. This would support a view that the required compliance, proposed by those in the current study, could also be viewed by services as a need for 'engagement', locating the problem within the service user.…”
Section: Conditions Of Helpmentioning
confidence: 99%
“…Several investigators have documented perceptions among homeless adults and identified key issues related to lack of compassion and empathy from service providers (Nickasch & Marnocha, 2009; Salem & Ma-Pham, 2015). The literature also reveals a need for health-promoting homeless–provider relationships (Oudshoorn, Ward-Griffin, Forchuk, Berman, & Poland, 2013).…”
Section: Changing Landscape: Health and Social Delivery Needsmentioning
confidence: 99%
“…Without doubt, negative provider attitudes toward homeless clients can act as barriers to quality health care and affect those experiencing homelessness. Homeless clients have listed respect, actively seeking ways to lessen the power differential, a nonjudgmental approach, and solidarity as the key components of the patient–provider relationship (Oudshoorn, Ward-Griffin, Forchuk, et al, 2013). Another study of provider perceptions revealed that HW described experiences with service providers as neutral, dehumanizing (e.g., unmet expectations, judged, minimized, alienated, powerless), or humanizing (e.g., cared for, trusted, shared past/identity, empowered; Biederman & Nichols, 2014).…”
Section: Changing Landscape: Health and Social Delivery Needsmentioning
confidence: 99%
“…Existing evidence suggests that many PEH have negative experiences of care, both within housing services (Stevenson, 2014) and healthcare settings (Oudshoorn et al , 2013). The conditionality of housing and support left PEH feeling disillusioned and hesitant to seek help (Jost et al , 2014), preventing PEH from trusting and engaging with services and workers (Zerger et al , 2014).…”
Section: Introductionmentioning
confidence: 99%